Pure Red Cell Aplasia (PRCA) and Cerebellar Hypoplasia as Atypical Features of Polyglandular Autoimmune Syndrome Type I (APS-1): Two Sisters With the Same AIRE Mutation but Different Phenotypes - Chinello, Matteo; Mauro, Margherita; Cantalupo, Gaetano; Balter, Rita; De Bortoli, Massimiliano; Vitale, Virginia; Zaccaron, Ada; Bonetti, Elisa; Gaudino, Rossella; Fiorini, Elena; Cesaro, Simone (Frontiers in Pediatrics, 2019)
The polyglandular autoimmune syndrome type I is a rare hereditary autosomal recessive disease. We describe a child with the classic triad of the disease and her sister with pure red cell aplasia and cerebellar hypoplasia. The latter received two haematopoietic stem cell transplantations, complicated by an acute disseminated encephalomyelitis.